Disseminated Mucormycosis in an Immunocompromised Patient with Richter Transformation of Chronic Lymphocytic Leukemia: A Case Report of Concurrent Findings on [18F]-Fluorodeoxyglucose PET-CT - Palsapure, Abhishek; Suthar, Ritesh R.; Rajkotia, Saloni (World Journal of Nuclear Medicine, 2025)
A case of chronic lymphocytic leukemia/small lymphocytic lymphoma with Richter transformation. After initiating R-CHOP chemotherapy, patient developed severe neutropenia and necrotizing cellulitis, necessitating an above-knee amputation. Subsequent positron emission tomography-computed tomography (PET-CT) imaging revealed new lesions suggestive of an abscess, confirmed as mucormycosis upon biopsy. This report highlights the importance of fludeoxyglucose PET-CT in detecting fungal infections in immunocompromised patients and its role in disease management.
Keywords: FDG PET/CT; infection; lymphoma; mucormycosis; Richter transformation